Hybridity in Bapsi Sidhwa's an American Brat and H.M. Naqvi's home boy - Gul, Hina (2016)
As immigrant fiction continues to emerge from the South Asian diaspora across the globe, theories of gender and identity that mostly treat such novels as Bildungsromans are often used to bring to light the plight of literary characters caught between two different cultures. Similar is the case with the novels An American Brat by Bapsi Sidhwa and Home Boy by H.M. Naqvi. Sidhwa and Naqvi are both Pakistani novelists who have experienced immigration to the United States, as do the main characters in their novels. However, while the two selected novels are united in their setting which is the US, there is a major difference in the time period that the stories are set in. An American Brat was written and published in a pre-9/11 America, and thus offers a different picture of life in the US than does Home Boy, a major part of which is set in a post-9/11 America. Both these novels are often read through the lens of the identity crisis that is experienced by the protagonists in them. Taking Homi K. Bhabha’s concept of hybridity as an analytical tool, however, this study uses mimicry, ambivalence, and unhomeliness, concepts under hybridity, to facilitate the understanding of the experiences and decisions of Feroza and Shehzad, the protagonists in the two novels. Besides studying if the three selected elements of hybridity can be found in the protagonists, this work also investigates whether or not they are responsible for their decisions to choose to stay either in Pakistan or in the United States at the end of the novels.